Suspected Adverse Drug Reactions of Selected Newly Introduced Medicines in Ambulatory Patients - A.P, Ravinandan; A, Ramesh (Indian Journal of Pharmacy Practice)
Each year, drug regulatory authority permits pharmaceutical companies to market hundreds of new medicines. During clinical trials, due to less number of study subjects, only commonly observed adverse drug reactions (ADRs) are reported. However in post marketing phase, more ADRs are observed due to various predisposing factors. Spontaneous reporting method is considered to be easy, economical and more reliable method to detect more number of ADRs. As research studies have corroborated the high incidence rate of ADRs in ambulatory patients, community pharmacists (CPs) can play an important role in monitoring and reporting suspected ADRs. The present prospective study was focussed to study adverse drug reactions (ADRs) of newly introduced medicines in ambulatory patients through community pharmacists. The selected community pharmacists were trained about monitoring and reporting of ADRs to the selected newly introduced medicines. Collected ADRs reports were assessed for causality, severity and preventability. Fourteen trained community pharmacists reported 63 ADRs in 4 months period. Twenty two ADRs were observed with pregabalin (34.92%) followed by voglibose 18 (28.57%), torsemide 09 (14.28%), doxofylline 05 (7.93%), zonisamide 03 (4.76%), moxonidine 02 (3.17%), rupatidine 02 (3.17%), simvastatin 02 (3.17%). The common adverse effects observed were dry mouth, constipation, dizziness and the main organ system affected was gastrointestinal system with 31 ADRs. Most of the reactions were predictable (95.23%) and moderate in their severity level (22.22%). Reporting of ADRs occurred in ambulatory patients to newly introduced medicines in community pharmacies will help to know the safety information about the medicines.
Keywords: Community pharmacists; Adverse Drug Reactions; Newly introduced medicines; Ambulatory patients